Structural analysis of the synthetic Duffy Binding Protein (DBP) antigen DEKnull relevant for Plasmodium vivax malaria vaccine design. - Edwin Chen; Nichole D Salinas; Francis B Ntumngia; John H Adams; Niraj H Tolia (Public Library of Science (PLoS), 2015)
The Plasmodium vivax vaccine candidate Duffy Binding Protein (DBP) is a protein necessary for P. vivax invasion of reticulocytes. The polymorphic nature of DBP induces strain-specific immune responses that pose unique challenges for vaccine development. DEKnull is a synthetic DBP based antigen that has been engineered through mutation to enhance induction of blocking inhibitory antibodies. We determined the x-ray crystal structure of DEKnull to identify if any conformational changes had occurred upon mutation. Computational and experimental analyses assessed immunogenicity differences between DBP and DEKnull epitopes. Functional binding assays with monoclonal antibodies were used to interrogate the available epitopes in DEKnull. We demonstrate that DEKnull is structurally similar to the parental Sal1 DBP. The DEKnull mutations do not cause peptide backbone shifts within the polymorphic loop, or at either the DBP dimerization interface or DARC receptor binding pockets, two important structurally conserved protective epitope motifs. All B-cell epitopes, except for the mutated DEK motif, are conserved between DEKnull and DBP. The DEKnull protein retains binding to conformationally dependent inhibitory antibodies. DEKnull is an iterative improvement of DBP as a vaccine candidate. DEKnull has reduced immunogenicity to polymorphic regions responsible for strain-specific immunity while retaining conserved protein folds necessary for induction of strain-transcending blocking inhibitory antibodies.